2006
DOI: 10.1177/0363546506289881
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Rotator Interval Closure

Abstract: This study suggests that the initial effect of arthroscopic rotator interval closure on anterior translation of the shoulder will be similar whether 1 or 2 sutures are used. In vivo studies are necessary to determine if the effect of these 2 methods would be the same over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Plausinis et al . 5 demonstrated that arthroscopic RI closure with 1-2 sutures significantly reduced A-P glenohumeral translation by 17% at neutral rotation (with respect to forearm) and at 0º abduction. Authors did not observe significant reduction in posterior translation.…”
Section: Biomechanical Studies Of Ri Closure and Its Effects On Ghjmentioning
confidence: 96%
“…Plausinis et al . 5 demonstrated that arthroscopic RI closure with 1-2 sutures significantly reduced A-P glenohumeral translation by 17% at neutral rotation (with respect to forearm) and at 0º abduction. Authors did not observe significant reduction in posterior translation.…”
Section: Biomechanical Studies Of Ri Closure and Its Effects On Ghjmentioning
confidence: 96%
“…Interval closure is controversial [ 65 , 66 , 71 ]. We perform this procedure when there is a sign of a 2 cm groove or when, after repairing an instability, a groove sign > 1 cm with the arm externally rotated persists [ 57 , 67 ].…”
Section: Interval Closurementioning
confidence: 99%
“…The closure of the rotator interval has been proposed as a technique to reduce recurrence rates. Recent biomechanical studies have not shown that the arthroscopic rotator interval closure is beneficial for the treatment of posterior glenohumeral instability [ 26 , 71 ].…”
Section: Complicationsmentioning
confidence: 99%
“… 48 , 50 , 58 Specifically, some suggest that injuries to the RI are associated with increased glenohumeral translation and that surgical imbrication of the RI may augment the repair construct during multidirectional and posterior stabilization. 12 , 17 , 24 , 31 , 43 , 54 , 71 , 78 …”
mentioning
confidence: 99%
“…One concern with performing RI plication, particularly in cases in which the procedure is unnecessary, is the potential for postoperative loss of external rotation. 54 , 57 , 71 , 78 Historically, RI plication was performed via open surgical approaches; however, all-arthroscopic techniques for RI plication have more recently been described. 10 , 12 , 16 , 32 , 35 , 44 , 66 , 69 Of note, open and arthroscopic RI closure are different surgical procedures and plicate different tissues, each in a different biomechanical vector.…”
mentioning
confidence: 99%